„COUPER LE SIEGE”. SUR LA REORGANISATION SYMBOLIQUE DE LA SALLE D’AUDIENCE - DUMITRACHE, Solange Ingrid Marina (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
Breaking the Chair. About the Symbolic Reorganisation of the Trial. On July 23, 2018, the article 7 of Law no. 304/2004 about the judicial organisation was completed as follows: the configuration of the court room must reflect the principle of the equality of arms concerning the position of the judge, the prosecutor and the lawyers. This paper aims to treat about the symbolic connotations of the rearrangement of the position of the main procedural actors in the space destinated to the act of judging, meaning the relocation of the prosecutor in line with the lawyer, with his back on the audience – as a visual sign of the equidistance of the judge regarding both of them.